Effect of Cash Management on Financial Performance of Kenya Power and Lighting Company in the Central Rift Region - Ochieng, Giriago Joseph; Ghabon, Yasin Kuso (PT. Riset Press International, 2025)
Cash management, a critical internal control mechanism, ensures liquidity, accountability, and operational efficiency in public utilities like Kenya Power and Lighting Company (KPLC). This study examines the effect of cash management practices on KPLC’s financial performance in the Central Rift Region, measured by Return on Assets (ROA). Guided by Agency Theory, a descriptive research design targeted 155 finance division staff across Nakuru, Narok, and Kericho sub-regions. Using stratified random sampling, data were collected from 53 respondents (85% response rate) via structured questionnaires with a five-point Likert scale. Validity was ensured through expert review, and reliability was confirmed with a Cronbach’s alpha of 0.787 for cash management items. Data analysis utilized descriptive statistics (means, standard deviations) and inferential statistics (Pearson correlation, regression) via SPSS. Ethical standards, including informed consent and confidentiality, were upheld. Findings reveal a significant positive correlation (r = 0.431, p < 0.05) between cash management and financial performance, with regression results showing a notable effect (β = 0.271, p = 0.009), explaining 77% of variance (R² = 0ros). Gaps in advanced budgeting tools and staff training were identified. The study concludes that effective cash management enhances financial performance by improving liquidity and accountability, recommending automated budgeting systems, regular training, and periodic audits to optimize outcomes.